Regional Development and Disparities in Jaunpur District, Uttar Pradesh - Kumar, Dinesh; Mishra, S. P. (National Geographical Journal of India, 2022)
Regional development is concerned with uniform growth and overall development of any area according to its potentialities and capabilities. Regional disparity is the outcome of imbalanced regional development that varies from region to region depending upon socio-cultural, economic and demographic characteristics.This paper attempts to deal with the analysis of regional development and disparities in Jaunpur district of Uttar Pradesh.The study area is situated in Eastern Uttar Pradesh of the Middle Ganga Plain.The study is exclusively based on secondary data collected at block level from different offices.The data were tabulated and analyzed using statistical methods like mean, standard deviation (SD), Z score and inter correlation matrix. Micro Soft excel and Arc GIS 10.2 software have been used for computation and cartographic presentation.There are 38 variables selected from four sectors (social, agricultural, infrastructural and industrial) to measure the regional disparities in the levels of development. The analysis reveals that Dharmapur and Sikrara blocks hold top position in high level of development while Shahganj block is at the bottem in terms of low level of development.The geographical factors like terrain condition, quality of soil, drainage, water logging, transport network and urban centers have been observed to hold major impact in the level of development in district.